An Asynchronous Data Transmission Method in Heterogeneous Wireless Networks. (14th October 2020) - Wang, Changhao; Li, Shining; Li, Bingqi; Chen, Qianwu
Abstract : With the massive deployment and application of intelligent systems such as smart life, smart medical care, and smart transportation, it is becoming more common for heterogeneous wireless networks such as WiFi, Zigbee, and Bluetooth to coexist in the same physical space. To improve the communication efficiency under the coexistence of heterogeneous wireless networks, this paper proposes an asynchronous data transmission method based on CTC technology, which constantly monitors the sleep and wake-up cycles of heterogeneous devices, makes full use of the wake-up cycle of the receiving terminal, and uses asynchronous methods to achieve cross-technology transmission of data packets. We also give a specific implementation scheme and use the program to simulate the transmission effect. The results show that our proposed method effectively reduces data transmission time and balances channel transmission throughput.